2013
DOI: 10.1248/bpb.b12-00915
|View full text |Cite
|
Sign up to set email alerts
|

Paracellular Barrier and Tight Junction Protein Expression in the Immortalized Brain Endothelial Cell Lines bEND.3, bEND.5 and Mouse Brain Endothelial Cell 4

Abstract: 1) These endothelial cells express specific ion and peptide transporters, which form a transcellular barrier; they also form a paracellular barrier owing to the presence of tight junctions between adjacent endothelial cells.2) The BBB contributes to homeostasis of the central nervous systems (CNS) by restriction of the transport of substances between brain and blood. Reliable in vitro BBB models are required for evaluations of the BBB function, especially the paracellular barrier.Recently, many immortalized br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(72 citation statements)
references
References 13 publications
(14 reference statements)
4
67
1
Order By: Relevance
“…However, endothelial cell lines cannot fully substitute for primary cells as important properties are changed that intermingle with the transferability of experimental findings to the in vivo situation. For instance, the murine brain endothelial cell line bEnd.5 expresses only low levels of discontinuously distributed tight junction proteins leading to high paracellular permeability 23 . BEnd.3, another frequently used murine brain endothelial cell line, demonstrates dense and continuous distributed tight junctions, a high transendothelial resistance, several efflux transporters and low paracellular permeability.…”
Section: Representative Resultsmentioning
confidence: 99%
“…However, endothelial cell lines cannot fully substitute for primary cells as important properties are changed that intermingle with the transferability of experimental findings to the in vivo situation. For instance, the murine brain endothelial cell line bEnd.5 expresses only low levels of discontinuously distributed tight junction proteins leading to high paracellular permeability 23 . BEnd.3, another frequently used murine brain endothelial cell line, demonstrates dense and continuous distributed tight junctions, a high transendothelial resistance, several efflux transporters and low paracellular permeability.…”
Section: Representative Resultsmentioning
confidence: 99%
“…Since T cell-specific inactivation of calnexin did not recapitulate the resistance to EAE exhibited by mice with global calnexin deficiency, we examined the transmigration of T cells across the blood-brain barrier using bEND.3 cells as a model of brain endothelial cells (29). Canx -/--bEND.3 cells showed normal responses to stimulation by cytokines with respect to upregulation of cell adhesion molecules but failed to support transendothelial migration of T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we asked if the function of the blood-brain barrier was altered in the absence of calnexin and whether this was responsible for protection of Canx -/-mice against EAE induction. To address this question, we used a mouse brain endothelial cell line, bEND.3 (28,29), which serves as a cell culture model for studies of the blood-brain barrier endothelium. First, we found that cytokine-stimulated bEND.3 CNS endothelial cells displayed an increased abundance of calnexin immunoreactivity ( Figure 7A).…”
Section: Transendothelial Migration Of T Cells Across the Brain Endotmentioning
confidence: 99%
“…Homocysteine-induced BBB disruption model in bEnd.3 cells was confirmed by analyzing paracellular and transcellular transport systems using Lucifer yellow and BSA-647 fluorescence probes leakage at different time points (10,20,40,60, 120 minutes) in four treatment groups. In Hcy-treated cells, significant endothelial cell permeability was observed, as evident through increased leakage of the Lucifer yellow (at 40 minutes and 60 minutes; Figure 1A) and BSA-647 (at 40 minutes to 120 minutes; Figure 1B) fluorescent dyes, which suggested that both paracellular and transcellular transport systems are affected during endothelial disruption.…”
Section: Confirming Blood-brain Barrier Disruption In Bend3 Cells Anmentioning
confidence: 96%